The Influence of Islamic Financial Literacy, Social Environment, and Public Perception on the Interest in Using Islamic Banking Products - Pebrianti, Gita Nuralipah; Syarief, Mochamad Edman (Journal of Applied Islamic Economics and Finance, 2025)
This study aims to analyze the influence of Islamic financial literacy, social environment, and public perception on the interest in using Islamic banking products among Muslim communities, particularly Generation Z in the Greater Bandung area. Data was collected through an online questionnaire distributed using a purposive sampling method, resulting in a total of 214 respondents. The data were analyzed using the Structural Equation Modeling (SEM) approach with the WarpPLS application to examine the relationships between the studied variables. The results indicate that Islamic financial literacy, social environment, and public perception significantly influence public interest in using Islamic banking products. These findings contribute significantly to the development of marketing strategies and Islamic financial education, particularly in the Greater Bandung area. The study also recommends enhancing Islamic financial literacy, strengthening the influence of the social environment, and managing positive public perception as strategic steps to expand the market share of Islamic banks in Indonesia.